EFFECT OF ASTRIGEN HERBAL PIPERBETLE LINN AGAINST ACCELERATING WOUND HEALING PERINIEUM AGAINST MOTHER IN RULING ON WORKING AREA HEALTH CENTER BANYUURIP KABUPATEN PURWOREDJO - Tri Puspa Kusumaningsih (Jurnal Komunikasi Kesehatan, 2014)
Background: Childbirth is a physiological process that often cause injuries to the birth canalcan potentially cause infection. Prevention of infection can be done by washing using theconservative anti-septic liquid on dirty wound contamination and wound infection by usingboiled water betel leaf.Objektive: To determine the effect of betel leaf decoction (astrigen Herbal Piperbetle Linn)Against Accelerating Wound Healing perinium On Mother's Ruling On Working Area HealthCenter Banyuurip Kabupaten Purworejo.Methods: This study is the study design Quasy experimental research Measure RandomizedControl Group Design. Research was using the intervention group 17 respondents with theapproach of Post Test Only Control Group.Results: The frequency of the old perineal healing in group betel leaves largely recoveredbetween 3-7 days to as much as 82.4 % , while in the same group also providin iodine largelyrecovered between 3-7 days to as much as 88.2 % . There is the influence of betel leafdecoction (astrigen Herbal Piperbetle linn) to accelerate wound healing perinium puerperalwomen Puskesmas Banyuurip Purworejo.Conclusion: There is an effect of betel leaf decoction (astrigen Herbal Piperbetle linn) toaccelerate wound healing perinium puerperal women Puskesmas Banyuurip Purworejo.Suggestion: for the people need to independently perform perineal wound care with existingresources in the vicinity. For educational institutions need to improve laboratory testresearch on betel leaf decoction.